The role of nuclear medicine in the diagnosis of Erdheim–chester disease. A series of clinical observations - A. S. Krylov; A. D. Ryzhkov; A. A. Odzharova; Ya. A. Shchipakhina; E. E. Stanyakina; A. A. Martinovich; K. D. Ilkaev; A. M. Stroganova; S. L. Dranko; O. P. Bliznyukovv; A. V. Kuzin; P. A. Zeynalova; et al. (Онкогематология, 2020)
Erdheim–Chester disease (ECD) is a rare disease with a poor prognosis. The first two cases were reported by Jakob Erdheim and William Chester in 1930. The etiology and disease incidence are unknown. One of the main components of this disorder is a chronic uncontrollable inflammation. In 2016 ECD was classified as histiocytic neoplasm by the World Health Organization and was categorized as “tumors of histiocytes and dendritic cells”. More than half of patients testing positive for the BRAF mutation. The final diagnosis is made on the basis of histological finding. There are radiological markers indicating a possible association with the disease. This is a specific, almost pathognomonic scintigraphic picture of the skeleton, “coated” aorta, “hairy” kidney patterns on computer tomography. There is a Erdheim–Chester Disease Global Alliance (ECDGA), which try to unite and provide with information about diagnostics and treatment of this rare disease both patients and doctors. Today, there are 571 registered patients and only one from Russia. We demonstrate three clinical cases of patients with newly diagnosed ECD and the role of nuclear medicine methods in assessing the prevalence of this disease.